2023
DOI: 10.1007/s11920-023-01445-5
|View full text |Cite
|
Sign up to set email alerts
|

Disgust Processing and Potential Relationships with Behaviors in Autism

Aditya Jayashankar,
Lisa Aziz-Zadeh

Abstract: Purpose of Review While there are reports of differences in emotion processing in autism, it is less understood whether the emotion of disgust, in particular, plays a significant role in these effects. Here, we review literature on potential disgust processing differences in autism and its possible associations with autistic traits. Recent Findings In autism, there is evidence for differences in physical disgust processing, pica behaviors, attention away f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 180 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The current data helps provide a mechanistic explanation for common ASD differences in brain activity (MCC, insula) and behavior (disgust sensitivity). 42,47 Further, in the ASD group, we speci cally found several correlations between indole metabolites, brain activity (insular subregions, aMCC/dmPFC, IFGop, and S1), and symptomatology (autism severity [ADI-R RSI] and alexithymia). Most interestingly, supporting our second hypothesis, we found that disgust processing activity in the right mid-insula mediates the relationship between indolelactate and two measures of autism severity (ADOS total score and ADOS RRBs).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The current data helps provide a mechanistic explanation for common ASD differences in brain activity (MCC, insula) and behavior (disgust sensitivity). 42,47 Further, in the ASD group, we speci cally found several correlations between indole metabolites, brain activity (insular subregions, aMCC/dmPFC, IFGop, and S1), and symptomatology (autism severity [ADI-R RSI] and alexithymia). Most interestingly, supporting our second hypothesis, we found that disgust processing activity in the right mid-insula mediates the relationship between indolelactate and two measures of autism severity (ADOS total score and ADOS RRBs).…”
Section: Discussionmentioning
confidence: 74%
“…Most interestingly, supporting our second hypothesis, we found that disgust processing activity in the right mid-insula mediates the relationship between indolelactate and two measures of autism severity (ADOS total score and ADOS RRBs). This is particularly noteworthy given that: 1) disgust processing is strongly related to interoceptive processing, making it particularly suited for gut metabolite in uence; 2) autistic children commonly have differences in disgust processing; 42,47 and 3) the mid-insula is a hub of interoceptive, emotion, and chemosensory processing, and is particularly known to show atypical activity and connectivity in ASD. [47][48][49] Thus, these data strongly support the notion that tryptophan-related gut metabolites impact brain function, contributing to some ASD behavioral symptomatologies.…”
Section: Discussionmentioning
confidence: 99%
“…The responses were categorized into 15 groups, including focal emphasis, contrastive emphasis, seven affects (joy, surprise, fear, sadness, anger, disgust, and contempt), fast/slow speaking rate, immediate/delayed response, and high/low voice volume. The seven affects are selected by adding six affects proposed by Ekman (1984) on "contempt," which means the aversion to humans because affects toward humans are considered to be necessary to study the pathophysiology of ASD (Jayashankar & Aziz-Zadeh, 2023).The English translation of each script is given in Table 1. There were two scripts for each affect except for anger, disgust, and contempt, for which there were three, one, and one script, respectively.…”
Section: Reading Materialsmentioning
confidence: 99%